2013
DOI: 10.12811/kshsm.2013.7.2.053
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Effects upon Satisfaction, Intention to Revisit and Perceived Value by Cerebrovascular Disease Patients through the Quality of Medical Services

Abstract: This study aims to analyze the effect of quality of health care on perceived value, patient satisfaction and revisit intention. Especially, it was focused on outdoor environment, admission procedure, hospital image, service quality of physicians that patients perceived.For inpatients, hospital image and service quality of medical technicians have an effect on perceived value. Service quality of physicians has an effect on the patient satisfaction. For outpatients, hospital image and service quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…We discovered that customer satisfaction of medical services had a positive (+) effect on revisit intention. This is consistent with previous studies, when a positive attitude toward service quality is formed, customers are satisfied, and then the intention to reuse the service also increases [19,43,45]. However, the impact of tangibles on customer satisfaction is not significant, which differs from the results of previous studies conducted by Kim and Kim [20] and Wi et al [5].…”
Section: Theoretical Implicationssupporting
confidence: 90%
See 3 more Smart Citations
“…We discovered that customer satisfaction of medical services had a positive (+) effect on revisit intention. This is consistent with previous studies, when a positive attitude toward service quality is formed, customers are satisfied, and then the intention to reuse the service also increases [19,43,45]. However, the impact of tangibles on customer satisfaction is not significant, which differs from the results of previous studies conducted by Kim and Kim [20] and Wi et al [5].…”
Section: Theoretical Implicationssupporting
confidence: 90%
“…Despite the fact that medical services require more expertise than other services, they include most of the characteristics of general services, so the concepts and theories developed in service marketing can be applied [17]. There are many studies on patient satisfaction and revisit intention by using a SERVQUAL model in the medical service field [6,[17][18][19][20][21]. Kim et al [18] conducted multiple regression analyses to investigate the relationship among medical service quality, revisit intention, and word of mouth, and, as a result, they found that assurance, responsiveness, and tangibles affect revisit intention.…”
Section: Medical Service Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…보건의료서비스가 모든 국민에게 공평하게 분배되고 기본적인 보 건의료서비스의 이용이 최대한 보장될 수 있도록 하기 위하여 국가는 공공정책을 통하여 보건의료체계를 마련하고 6) , 한정된 의료서비스 자 원을 균등하게 분배하여 적절하게 이용해야 한다 7) . 이런 맥락에서 구 강보건 증진을 위해서는 국가는 구강보건의료인력을 합리적으로 기획 하고 효율적으로 관리하여야 한다 8) .…”
Section: 서 론unclassified